2018
DOI: 10.1111/jcal.12335
|View full text |Cite
|
Sign up to set email alerts
|

A gender matching effect in learning with pedagogical agents in an immersive virtual reality science simulation

Abstract: The main objective of this study is to determine whether boys and girls learn better when the characteristics of the pedagogical agent are matched to the gender of the learner while learning in immersive virtual reality (VR). Sixty‐six middle school students (33 females) were randomly assigned to learn about laboratory safety with one of two pedagogical agents: Marie or a drone, who we predicted serve as a role models for females and males, respectively. The results indicated that there were significant intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 46 publications
(122 reference statements)
5
58
1
Order By: Relevance
“…Additionally, in coordination with our design focus around representing students' identities within the visual and auditory cues among our VR 360 videos, Makransky, Wismer, and Mayer () found that the role of the digital identity representations in a VR platform becomes a factor in shaping students' connections to the discipline, wherein they also explain that VR can enhance the learners' experience by changing who is involved in the teaching and showcase specifically how gender representations in VR had a differential impact on students' attitudes toward learning. In our study, while we did not find such an impetus from our participants' self‐reports to represent students' identities in relation to how the content may be relevant to them, we did find that students in our Control condition—the condition designed with visual and auditory cues to not look and sound like the students or their communities—reported an uneasiness about the lesson, showcasing that our purposeful decontextualization and lack of familiarity may have influenced these students' attitudes toward the relevancy of science.…”
Section: Implications and Principal Contribution To The Fieldmentioning
confidence: 88%
“…Additionally, in coordination with our design focus around representing students' identities within the visual and auditory cues among our VR 360 videos, Makransky, Wismer, and Mayer () found that the role of the digital identity representations in a VR platform becomes a factor in shaping students' connections to the discipline, wherein they also explain that VR can enhance the learners' experience by changing who is involved in the teaching and showcase specifically how gender representations in VR had a differential impact on students' attitudes toward learning. In our study, while we did not find such an impetus from our participants' self‐reports to represent students' identities in relation to how the content may be relevant to them, we did find that students in our Control condition—the condition designed with visual and auditory cues to not look and sound like the students or their communities—reported an uneasiness about the lesson, showcasing that our purposeful decontextualization and lack of familiarity may have influenced these students' attitudes toward the relevancy of science.…”
Section: Implications and Principal Contribution To The Fieldmentioning
confidence: 88%
“…The desktop and immersive VR versions of the VR laboratory safety simulations were developed by the simulation development company Labster (see Labster, , for an introduction to the simulation). The main learning objective of the simulations was knowledge about laboratory safety and lab safety skills and has been described in previous educational technology research (e.g., Makransky et al, ). Four types of knowledge based on Mayer's () five kinds of knowledge taxonomy were the focus of the simulations including facts (e.g., the definition of important hazard symbols in a lab presented in the top right frame of Figure ), concepts (e.g., it may be dangerous to wear contact lenses because chemicals may get trapped behind them), procedures (e.g., the step by step process of what you should do in case of a simple spill of a corrosive chemical), and beliefs (e.g., building self‐efficacy by providing positive feedback after successfully completing a task).…”
Section: Methodsmentioning
confidence: 99%
“…The use of VR as a platform to deliver educational content is one example of an educational technology that has increasingly been used in education over the last decade (Blascovich & Bailenson, ; Dawley & Dede, ; Makransky, Terkildsen, & Mayer, ; Makransky, Wismer, & Mayer, ; Parong & Mayer, ; Standen & Brown, ; van Ginkel et al, ). The growing availability of commercially available head‐mounted displays (HMDs) means that educational and training applications of VR are now readily accessible to the general public (Buttussi & Chittaro, ).…”
Section: Introductionmentioning
confidence: 99%
“…British Journal of Educational Technology Vol 51 No 6 2020 of the importance of feedback in learning through the Labster simulations used in this study . This feedback can be accomplished by providing retrieval practice activities through multiple-choice questions and by providing feedback using a pedagogical agent in IVR (Makransky, Wismer & Mayer, 2018).…”
mentioning
confidence: 99%